2019
DOI: 10.1590/0001-3765201920180171
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cytotoxicity and wound healing activity of Avicennia schaueriana in cream

Abstract: Avicennia schaueriana is found in Brazilian mangrove coast. the cytotoxicity in vitro of the Aqueous extract of leaves of Avicennia schaueriana (AelAs) and the healing activity of the plant in cream on mice skin wounds were evaluated in this study. the cytotoxic evaluation was performed on Vero cells. the healing activity was evaluated on mice treated during 5, 10 and 15 days with cream at 5%, solution of sodium chloride at 0.9% and dexpanthenol in cream at 5%. the extract did not show cytotoxicity, but showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Along similar lines, Araújo (2015) developed a healing cream of the aqueous extract of R. mangle leaves at a concentration of 5% that showed favourable results in tissue repair during in vitro and in vivo tests. The same 5% concentration was also used by Lopes et al (2019) to evaluate a healing cream with Avicennia schaueriana extract.…”
Section: Discussionmentioning
confidence: 99%
“…Along similar lines, Araújo (2015) developed a healing cream of the aqueous extract of R. mangle leaves at a concentration of 5% that showed favourable results in tissue repair during in vitro and in vivo tests. The same 5% concentration was also used by Lopes et al (2019) to evaluate a healing cream with Avicennia schaueriana extract.…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by three mechanisms (keratinocyte proliferation, fibroblast growth, and the preservation of growth factors), which improves wound healing under controlled hydration and a moist environment [ 53 ]. In addition to M. oleifera , other plant species, such as Avicennia schaueriana [ 54 ], Morinda tinctoria Roxb [ 55 ], and Albizia amara [ 56 ], have also been subjected to wound healing studies, wherein their aqueous leaf extract showed significant wound healing activity.…”
Section: Discussionmentioning
confidence: 99%